Welcome to Westonci.ca, your one-stop destination for finding answers to all your questions. Join our expert community now! Get quick and reliable solutions to your questions from a community of experienced experts on our platform. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.

Consider the following functions.f(x) = x + 4 and g(x) = x - 7=Step 2 of 4: Find (f - 3)(x). Simplify your answer.Answerf-8)(x) =

Consider The Following Functionsfx X 4 And Gx X 7Step 2 Of 4 Find F 3x Simplify Your AnswerAnswerf8x class=

Sagot :

Solution

[tex]\begin{gathered} f(x)=x+4 \\ g(x)=x-7 \end{gathered}[/tex]

Now

[tex]\begin{gathered} (f-g)(x)=x+4-(x-7) \\ (f-g)(x)=x+4-x+7 \\ (f-g)(x)=11 \\ \end{gathered}[/tex]

The final answer

[tex]11[/tex]

Thank you for trusting us with your questions. We're here to help you find accurate answers quickly and efficiently. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Thank you for visiting Westonci.ca. Stay informed by coming back for more detailed answers.